The Contribution of Neuromarketing to Knowledge about Advertising - an Attempt to Systematize Research Directions - Budzanowska-Drzewiecka, Małgorzata (Studia Oeconomica Posnaniensia, 2018)
The article attempts to describe the review of literature striving to systematize the contribution of neuromarketing research to the knowledge about advertising, and in particular its composition. Due to the adopted academic perspective (emphasizing the value of neuromarketing as a field), an effort was made to identify the interest areas which constitute current and potential directions for further exploration. The analysed research results available in the literature of the subject confirm the advantages of using this research approach to extend the knowledge in the area of advertising with varying levels of detail, both at the theoretical level and practical applications. At the same time, they emphasize the need for a further exploration of indicators allowing for the accurate assessment of advertisements using neuromarketing methods.